2010
DOI: 10.1042/bj20100383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new series of non-covalent proteasome inhibitors with exquisite potency and selectivity for the 20S β5-subunit

Abstract: The mammalian 26S proteasome is a 2500 kDa multi-catalytic complex involved in intracellular protein degradation. We describe the synthesis and properties of a novel series of non-covalent di-peptide inhibitors of the proteasome used on a capped tri-peptide that was first identified by high-throughput screening of a library of approx. 350000 compounds for inhibitors of the ubiquitin–proteasome system in cells. We show that these compounds are entirely selective for the β5 (chymotrypsin-like) site over the β1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(177 citation statements)
references
References 53 publications
11
157
0
9
Order By: Relevance
“…Hence, the β1i active site preferentially cleaves proteins C-terminally of small hydrophobic and branched amino acids such as Leu, Ile or Val and significantly enhances the production of high-affinity MHC I ligands. The structural features of subunit β1i are in full agreement with the reported β1i-selective fluorogenic substrate Ac-Pro-Ala-Leu-AMC [110] . In addition to the changes in the S1 pocket, the S3 pocket is characterized by the amino acid substitutions T22A (β1i) and A27V (β1i) as well as Y114H in the neighbouring subunit β2i.…”
Section: Structural Analysis Of the Substrate Binding Channelssupporting
confidence: 74%
See 1 more Smart Citation
“…Hence, the β1i active site preferentially cleaves proteins C-terminally of small hydrophobic and branched amino acids such as Leu, Ile or Val and significantly enhances the production of high-affinity MHC I ligands. The structural features of subunit β1i are in full agreement with the reported β1i-selective fluorogenic substrate Ac-Pro-Ala-Leu-AMC [110] . In addition to the changes in the S1 pocket, the S3 pocket is characterized by the amino acid substitutions T22A (β1i) and A27V (β1i) as well as Y114H in the neighbouring subunit β2i.…”
Section: Structural Analysis Of the Substrate Binding Channelssupporting
confidence: 74%
“…pockets, the β5i subunit prefers more spacious ones than subunit β5c [110] (see also chapter 6.3.3).…”
Section: Figure 16 Superposition Of the Unprimed β5c And β5i Substratmentioning
confidence: 99%
“…The synthetic route and methods of compound characterization were similar to those reported for N,C-capped dipeptidomimetics (15,28), with modifications as given in the supplemental online material. All compounds were >95% pure.…”
Section: Methodsmentioning
confidence: 91%
“…We cultured Karpas1106P B lymphoma cell line (catalog no. 06072607; Aldrich) (15), mouse bone marrow-derived macrophages (18), PBMCs (17,30), and HepG2 human hepatoma cells (31). Karpas cells were cultured in complete medium and the other cells in complete medium with 10% (vol/vol) FBS instead of 20% (vol/vol), all at 37°C in a humidified air/5% (vol/vol) CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that in proteasomes derived from livers of LCMV-infected mice, the three catalytically active constitutive subunits, b1, b2, and b5, are almost completely replaced by the immunoproteasome subunits LMP2, MECL-1, and LMP7 (36). LMP2-deficient and WT immunoproteasomes (from the livers of LCMV-WE-infected mice) were incubated with different concentrations of ML604440 and assayed with a fluorogenic substrate specific for LMP2 activity (Ac-PAL-AMC) (37) (Fig. 2B).…”
Section: Lmp2-selective Inhibition Does Not Alter Uty 246-254 Presentmentioning
confidence: 99%